Social work, social justice & human rights a structural approach to practice - Lundy, Colleen 1946- (University of Toronto Press, 2011)
"Social workers take pride in their commitment to social and economic justice, peace, and human rights and in their responses to related inequalities and social problems. The urgency of this kind of commitment increases as economic globalization, armed conflict, and ecological devastation continue to undermine human rights and the possibilities for social justice. The second edition of this popular social work text more fully addresses social justice and human rights and includes a discussion of the role of social work in promoting peace and responding to the environmental problems facing humanity. New chapters have been added on human rights, social work with immigrants and refugees, social work and mental health, and supporting couples and families. Detailed case studies throughout demonstrate the integration of theory and practice."--Publisher's website.